Diagnostic tests for COVID-19: The importance of the before and the after - Aguilar Ramírez, Priscilia (2020)
In 2019, in the city of Wuhan, China, patients were diagnosed with a novel coronavirus originally named 2019-nCoV, currently known as SARS-CoV-2. The alarming expansion of this pandemic makes it necessary to find out and implement reliable diagnostic methods in order to properly detect and treat patients, thus contributing to slowing down the spread of the disease. It is extremely important to have trained professionals in sample collection, good clinical laboratory practices, and molecular and hematological techniques to adequately detect any cases of infection with this virus. Moreover, standardized protocols are essential for obtaining, transferring and storing samples to stop the spread of the COVID-19 pandemic caused by SARS-CoV-2.